Effects of Modified Foot Abduction Brace in Maintaining the Foot Position after Ponseti Treatment Method in Congenital Clubfoot - Sona, Pornpimon; Kharmwan, Samerduen; Vipulakorn, Kitiwan; Sarntipiphat, Chatchawarl; Pannon, Atiwat (Srinagarind Medical Journal, 2024)
Objective: Modify the Foot Abduction Brace (FAB) and measure the slippage of the FAB to obtain a suitable FAB for maintaining the position of the patient's foot and to study of parents' satisfaction with modified FAB. Methods: An action research was conducted in 2 stage stage 1 Modify the FAB according to interdisciplinary consensus. Stage 2 twenty-nine patients with congenital clubfoot who have been treated with the Ponseti method will receive FAB from the outpatient rehabilitation department at Srinagarind Hospital to maintain foot shape for 7 days. Parents record FAB slippage, satisfaction, and problems encountered in using the modified FAB in the diary and telephone interviews. Results: Of the 29 congenital clubfoot patients, 21 were male (72.4%), with a mean age of 10.6 ± 7.9 months. The mean age at initiation of FAB usage was 21.2 ± 2.7 weeks. Fourteen patients (48.3%) started using the FAB for the first time. The study found that 69.0% - 79.3% of patients had no FAB slippage during usage. The average number of FAB slippages were 1.2 ± 2.4 times/day (median = 0, interquartile range 0-1). Parental satisfaction was reported at 4.7 ± 0.6 points, with the highest satisfaction regarding fit and durability (4.6 ± 0.6 and 4.6 ± 0.8, respectively). Conclusion: By modifying both the shoe and strapping of the FAB found minimal instances of FAB slippage. Moreover, the parents expressed high satisfaction in using the FAB, which was also cost-effective and covered by government reimbursement.